Comparison of two commercial dentifrices in the reduction of gingivitis and plaque: A pilot study - Kerbauy, Warley David (2017)
Objectives: Chlorhexidine (CHX) and triclosan are the most used chemical agents in dentistry. However, the combination of these products has never been tested. We hypothesize that the addition of CHX to a triclosan dentifrice formulation may offer additional benefits in the reduction of plaque and gingivitis. Thus, the aim of this study was to compare a commercial dentifrice containing 0.05% chlorhexidine and 0.3% triclosan, with conventional toothpaste containing 0.3% triclosan, in the treatment of gingivitis and plaque reduction. Material and Methods: Thirty volunteers were randomly assigned to receive a dentifrice containing 0.05% CHX and 0.3% triclosan (CHX/triclosan group) or a dentifrice containing basically 0.3% triclosan (Triclosan group). Subjects received clinical evaluation such as gingival index (GI) and plaque index (PI) at baseline, 30 and 60 days. Results: After 60 days, both treatments led to a significant improvement in GI and PI. There was no significant difference between groups as regards change in GI and PI (p>0.05). Conclusion: The combination of 0.05% CHX with 0.3% triclosan did not offer further benefits to gingival inflammation and plaque control when compared with a dentifrice containing 0.3% triclosan.KeywordsChlorhexidine; CHX dentifrice; Triclosan; Plaque; Gingivitis.